The values of the traditional culinary practices towards the modernization as perceived by the Malay Chefs in Klang Valley - Ismail, Nurul Ashikin; Abdul Karim, Muhammad Shahrim; Othman, Mohiddin; Abdul Halim, Norhasmilaalisa (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The central question to be examined in this study is associated with the value of the Malays traditional culinary practices of Malay chef in preparing the traditional food in Malaysian hotels. Present understanding highlighted that hotels are giving high priority on their superior services, such as luxury accommodations and intimate hospitalities. As such, promoting local foods in their dining establishment has taken a back seat. Research from past scholars indicated that hotel in Malaysia can be the one stop center for the local and international tourists to get the first hand information about local food specialities. On the hindsight, very limited efforts have been put into practice on the promotions of local food especially Malay cuisines in hotels. Main issue such as mass-produced Malay cuisines in the commercial kitchens, for example, should be highlighted to ensure that hotels are not jeopardizing the originality of traditional food preparations. Therefore, a qualitative reasearch focusing in in-depth interview with 10 Malay chefs was conducted in hotels around the Klang Valley. The results are so profound that majority of the Malay chefs under study shared similar understandings on technology advancements and modernizations that have taken place in their daily food preparations. Another finding revealed that one of the most challenging factors in preventing the Malay chefs to prepare the Malay food as it has been done traditionally is the attitude and awareness of the young generations to understand the values in traditional culinary practices. This study concludes with suggestion that aggressive knowledge sharing and information dissemination among the Malay chefs in hotels are needed to effectively market the traditional Malay food.